New inflammatory markers in diagnosing acute appendicitis (Annals of Medical Research, 2021)
Aim: Acute appendicitis (AA) is the most common cause of abdominal pain, acute abdomen and emergency abdominal operation. The diagnosis of AA is usually based on clinical history and physical examination. Assessment of the systemic inflammatory response of the neutrophil lymphocyte ratio (NLR) and platelet lymphocyte ratio (PLR), which can be achieved through a simple blood count such as a complete blood count, is shown as a new biomarker. The aim of our study is to examine whether readily available markers such as NLR, PLR, RDW, and MPV can be used to distinguish AA whether complicated and uncomplicated appendicitis cases.Materials and Methods: We retrospectively reviewed the patients who had been admitted to the Erzurum Regional Education and Research Hospital between January 2016 and June 2016 with abdominal pain complaints and applied appendectomy. Preoperative and postoperative CRP, leukocyte, RDW, neutrophil, platelet values were recorded. The NLO and PLO values were manually calculated from the complete blood count.Results: Preop NLR was found 5.58 ± 4.44 in the appendicitis group and 4.65 ± 4.93 in the complicated appendicitis group. Post op NLO values were 2.87 ± 1.76 and post op NLR in the appendicitis group. Postop NLO and CRP values significantly decreased compared to Preop values. ( p